Authenticity Perceptions in Global Luxury Consumption : A Consumer Culture Theory Perspective - Kalpio, Elsa (My University, 2026)
Globalization has changed the context in which luxury brands are encountered and in- terpreted. Consumers increasingly engage with luxury through global media, international marketing and symbolic cues. As a result, traditional luxury elements such as heritage, craftsmanship, exclusivity and provenance are no longer evaluated in isolation. Cultural background still matters, but authenticity is shaped through interaction between global brand meanings and local interpretation. Authenticity can therefore no longer be understood just as a fixed or origin-bound concept. This thesis examines how globalization influences consumers’ perceptions of authenticity in luxury branding. The study draws on literature related to globalization, global consumer culture and brand authenticity. It focuses on four key dimensions of authenticity: continuity, credibility, integrity and symbolic value. These dimensions are used to explain how consumers assess authenticity in global luxury markets. The synthesis shows that authenticity develops through the interaction of global brand narratives, cultural meaning systems and consumers’ identity-related interpretations. Shared global associations influence how luxury is understood, but cultural context continues to guide evaluation. For this reason, luxury brands must balance global consistency with culturally meaningful communication in different market settings.

Globalisaatio on muuttanut sitä kontekstia, jossa luksusbrändejä kohdataan ja tulkitaan. Kuluttajat ovat yhä useammin tekemisissä luksuksen kanssa globaalin median, kansainvälisen markkinoinnin ja symbolisten vihjeiden kautta. Tämän seurauksena perinteisiä luksuksen elementtejä, kuten perintöä, käsityötaitoa, eksklusiivisuutta ja alkuperää, ei enää arvioida erillään toisistaan. Kulttuuritausta on yhä merkityksellinen, mutta autenttisuus muotoutuu globaalien brändimerkitysten ja paikallisen tulkinnan vuorovaikutuksessa. Autenttisuutta ei voida enää ymmärtää pelkästään kiinteänä tai alkuperään sidottuna käsitteenä. Tämä tutkielma tarkastelee, miten globalisaatio vaikuttaa kuluttajien käsityksiin autenttisuudesta luksusbrändäyksessä. Tutkimus pohjautuu globalisaatiota, globaalia kuluttajakulttuuria ja brändiautenttisuutta koskevaan kirjallisuuteen. Se keskittyy neljään autenttisuuden keskeiseen ulottuvuuteen: jatkuvuuteen, uskottavuuteen, eheyteen ja symboliseen arvoon. Näitä ulottuvuuksia käytetään selittämään, miten kuluttajat arvioivat autenttisuutta globaaleilla luksusmarkkinoilla. Synteesi osoittaa, että autenttisuus kehittyy globaalien brändikertomusten, kulttuuristen merkitysjärjestelmien ja kuluttajien identiteettiin liittyvien tulkintojen vuorovaikutuksessa. Jaetut globaalit mielleyhtymät vaikuttavat siihen, miten luksus ymmärretään, mutta kulttuurinen konteksti ohjaa edelleen arviointia. Tästä syystä luksusbrändien on tasapainoteltava globaalin johdonmukaisuuden ja kulttuurisesti merkityksellisen viestinnän välillä eri markkinaympäristöissä.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|